Gender Identity and Assignment Recommendations in Disorders of Sex Development Patients: 20 Years' Experience and Challenges - Fatih Gürbüz; Murat Alkan; Gonca Çelik; Atıl Bişgin; Necmi Çekin; İlker Ünal; Ali Kemal Topaloğlu; Ünal Zorludemir; Ayşe Avcı; Bilgin Yüksel (Galenos Yayincilik, 2020)
Objective:Gender assignment in infants and children with disorders of sex development (DSD) is a stressful situation for both patient/families and medical professionals.Methods:The purpose of this study was to investigate the results of gender assignment recommendations in children with DSD in our clinic from 1999 through 2019.Results:The mean age of the 226 patients with DSD at the time of first admission were 3.05±4.70 years. 50.9% of patients were 46,XY DSD, 42.9% were 46,XX DSD and 6.2% were sex chromosome DSD. Congenital adrenal hyperplasia (majority of patients had 21-hydroxylase deficiency) was the most common etiological cause of 46,XX DSD. In 46,XX patients, 87 of 99 (89.7%) were recommended to be supported as a female, 6 as a male, and 4 were followed up. In 46,XY patients, 40 of 115 (34.8%) were recommended to be supported as a female, and 70 as male (60.9%), and 5 were followed up. In sex chromosome DSD patients, 3 of 14 were recommended to be supported as a female, 9 as a male. The greatest difficulty in making gender assignment recommendations were in the 46,XY DSD group.Conclusion:In DSD gender assignment recommendations, the etiologic diagnosis, psychiatric gender orientation, expectation of the family, phallus length and Prader stage were effective in the gender assignment in DSD cases, especially the first two criteria. It is important to share these experiences among the medical professionals who are routinely charged with this difficult task in multidisciplinary councils.